The Monetary Doctrines of Messrs. Foster and Catchings - Robertson, D. H. (Quarterly Journal of Economics, 1929)
I. The authors' thesis broken up into its constituent parts. Some criticisms of those parts which are not peculiar to the authors, 474. — II. The authors' distinctive doctrine of the connection of trade depression with the phenomena of profit and saving, 477. — The alternative hypothesis implicit in their earlier “Cases,” 479. — III. Critical analysis of their later “Cases” and of their theory of the operation of bankloans, 485.—IV. Criticism of the statistical evidence adduced in support of their theory. Summary and conclusion, 494.